Use of the Fogg Behavior Model to Assess the Impact of a Social Marketing Campaign on Condom Use in Pakistan. Issue 3 (4th March 2019) - Agha, Sohail; Tollefson, Deanna; Paul, Shadae; Green, Dylan; Babigumira, Joseph B.
Abstract : The Fogg Behavior Model (FBM) is a new framework which posits that behavior happens when three factors – motivation, ability, and a prompt – occur in the same moment. The FBM categorizes people into four groups based on motivation and ability and posits that those with high motivation and high ability will adopt a behavior when prompted. Two rounds of panel survey data from 617 married men in urban Pakistan were used to test this hypothesis. Multilevel mixed-effects logistic regression was used for the analysis. The results show the relationships between ability, motivation, the prompt and condom use to be as hypothesized by the FBM. After adjustment for a range of variables including fertility desires, education, and household wealth, the odds of condom use among men with high motivation and high ability were 34 times higher than the odds of condom use among men with low motivation and low ability. Moreover, the association between the prompt and condom use operated through increased motivation and ability. The FBM has potential for use in the design and evaluation of behavior change interventions in developing countries.